Free will, consciousness, and self : anthropological perspectives on psychology - Bertelsen, Preben (Studies in the understanding of the human condition., 2005)
"In this book, the author develops a general theoretical model that may offer a better understanding of underlying principles of human behavior. The author shows that general psychology can make a significant contribution to a general anthropology and the human condition."--BOOK JACKET.